Male partner age, viral load, and HIV infection in adolescent girls and young women: evidence from eight sub-Saharan African countries. (1st January 2023) - Ayton, Sarah; Schwitters, Amee; Mantell, Joanne E.; Nuwagaba-Biribonwoha, Harriet; Hakim, Avi; Hoffman, Susie; Biraro, Sam; Philip, Neena; Wiesner, Lubbe; Gummerson, Elizabeth; Brown, Kristin; Nyogea, Daniel; et al.
Abstract : Objective: We aimed to elucidate the role of partnerships with older men in the HIV epidemic among adolescent girls and young women (AGYW) aged 15–24 years in sub-Saharan Africa. Design: Analysis of Population-based HIV Impact Assessments in Eswatini, Lesotho, Malawi, Namibia, Tanzania, Uganda, Zambia, and Zimbabwe. Methods: We examined associations between reported partner age and recent HIV infection among AGYW, incorporating male population-level HIV characteristics by age-band. Recent HIV infection was defined using the LAg avidity assay algorithm. Viremia was defined as a viral load of more than 1000 copies/ml, regardless of serostatus. Logistic regression compared recent infection in AGYW with older male partners to those reporting younger partners. Dyadic analysis examined cohabitating male partner age, HIV status, and viremia to assess associations with AGYW infection. Results: Among 17 813 AGYW, increasing partner age was associated with higher odds of recent infection, peaking for partners aged 35–44 (adjusted odds ratio = 8.94, 95% confidence interval: 2.63–30.37) compared with partners aged 15–24. Population-level viremia was highest in this male age-band. Dyadic analyses of 5432 partnerships confirmed the association between partner age-band and prevalent HIV infection (male spousal age 35–44-adjusted odds ratio = 3.82, 95% confidence interval: 2.17–6.75). Most new infections were in AGYW with partners aged 25–34, as most AGYW had partners in this age-band. Conclusion: These results provide evidence that men aged 25–34 drive most AGYW infections, but partners over 9 years older than AGYW in the 35–44 age-band confer greater risk. Population-level infectiousness and male age group should be incorporated into identifying high-risk typologies in AGYW.